A 3-year study of patients with tinnitus and jaw muscle tenderness. Issue 5 (3rd September 2019) - Unell, Lennart; Ström, Dan; Ekman, Kristina; Johansson, Anders; Arnrup, Kristina; Carlsson, Gunnar E.
Abstract: Objective: This study evaluated three-year results of treatment with an interocclusal appliance in 89 tinnitus patients with jaw muscle tenderness. Methods: Subjective tinnitus severity was recorded using a visual analog scale (VAS). The number of tender muscles was registered. The patients were followed annually. After three years, 64 patients were examined (72%). Results: Tinnitus severity at baseline was high (mean VAS value 68.3). After one year, the VAS values were substantially lower (mean 37.4; p < 0.001). During the following two years, there were no significant changes in VAS values. The mean number of tender muscles decreased from seven to two after one year and remained at this number for up to three years. Conclusion: In many tinnitus patients with signs of temporomandibular disorders (TMDs), intraoral splint therapy reduced tinnitus severity and jaw muscle symptoms. The favorable results after one year remained for up to three years without significant changes.